Lost in transition?: the personal and professional challenges for probation leaders engaged in delivering public sector reform - Millings, Matthew (Probation journal, 2019)
The outsourcing and transfer of labour in the contexts of policing, prisons and courts illustrate that, even in a national context, these transitions are not uniform. Rather, there are a diverse set of ‘privatisation journeys’ that can be taken and that need to be understood. Our focus in this article is on the experience of probation leaders who, under the Transforming Rehabilitation (TR) reform programme, were charged with stewarding their organisation from the public sector, through a 10-month transitional period, and into the full relinquishing of ownership to the private sector. It is an account of how, with no clear ‘transition and transformation’ precedent to follow, a locally-based senior management team from one probation trust engaged with the task of implementing organisational change during a period of great uncertainty. We explore managers’ engagement with the language, working styles and vision of engineering transformational change and how they processed and began to articulate the challenges of new ownership, both for themselves (as individuals) and for their organisation (as a collective). We examine the resilience of the organisational culture at senior management level; the operational dynamism of leaders to embrace change; and the extent to which senior managers felt able to participate in, and take ownership of, the new Community Rehabilitation Company (CRC) they were charged with forming.